The clash of civilizations and the remaking of world order - Huntington, Samuel P. (Simon & Schuster, 2011)
"The central theme of this book is that culture and cultural identities, which at the broadest level are civilization identities, are shaping the patterns of cohesion, disintegration, and conflict in the post-Cold War world"--Page 20